2012
DOI: 10.1111/j.1440-1797.2011.01538.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycaemia emerging during general anaesthesia induces rat acute kidney injury via impaired microcirculation, augmented apoptosis and inhibited cell proliferation

Abstract: Anaesthesia-induced hyperglycaemia affects intra-renal auto-regulation via decreased renal perfusion, thus triggering renal function deterioration and tubular injury. Increased intra-renal Angiotensin-II aggravates the damage. Tight hypoglycaemic control might prevent or, at least, attenuate anaesthesia-induced renal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…In accordance with our previous observations 15,20 normal animals invariably developed acute transient hyperglycaemia minutes after induction of general anaesthesia. Insulin secretion continuously increased in response to hyperglycaemia, positively correlating with the latter.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In accordance with our previous observations 15,20 normal animals invariably developed acute transient hyperglycaemia minutes after induction of general anaesthesia. Insulin secretion continuously increased in response to hyperglycaemia, positively correlating with the latter.…”
Section: Discussionsupporting
confidence: 93%
“…[1][2][3][4][5]18,19 In clinical practice, postoperative inflammation is generally believed to result from surgical stress and intraoperative interventions. [1][2][3][4][5] Our previous experience 15,20 prompted us to speculate that surgery-induced stress might either aggravate or disguise the role of anaesthesia per se in postoperative renal complications. Therefore, we intentionally isolated the effects of anaesthesia from the impacts of either surgery or intraoperative maintenance, demonstrating that our results were inflicted by anaesthesia regardless of unspecific stress conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the precise mechanisms of insulin on mitochondrial oxidative stress remain to be fully elucidated. Hyperglycemia is common in sepsis and can also induce inflammation, oxidative stress and apoptosis in sepsis or AKI models ( 24 , 25 ). Previous studies revealed that insulin therapy exerts the protective effect against mitochondrial oxidative stress via lowering blood glucose levels ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, RMIC can be characterized as a capillary network with a proportion of perfused vessels reaching an average of 100% of all visible vessels and showing constantly continuous to hyperdynamic flow in all vessels as assessed by semiquantitative velocity classification. To our best knowledge, there are no similar studies evaluating RMIC by SDF imaging, however, some studies focus on changes in perfusion in different disease models and treatments (Mikhailichenko & Tikhomirova, ; Efrati et al ., ; Zhu et al ., ; Xu et al ., ). Understanding of renal microcirculation seems to play a crucial role in sepsis and acute kidney injury as the microcirculation is the integrative physiological compartment where all deleterious mechanisms come together and exert their integrative action that can be observed clinically (Le Dorze et al ., ; Ergin et al ., ).…”
Section: Discussionmentioning
confidence: 99%